RAS pathway and disease: neurofibromatosis and beyond - Legius, Eric (Henry Stewart Talks, 2014)
Neurofibromatosis type 1 (NF1), NIH diagnostic criteria (Seven criteria for NF1), NF1 and the RAS pathway, NF1 tumour biology, Neurofibromin deficiency, Two types of neurofibromas, Plexiform neurofibroma in the neck and mouth, Mechanisms of disease, Mouse models of neurofibroma formation, Imatinib mesylate treatment, Clinical aspects of glomus tumours of fingertips, Gastrointestinal stromal tumours, MPNST in NF1, FDG-PET as a diagnostic tool, Hotspots for recombination & NF1 microdeletion, SUZ12-loss, Cafe-au-lait (CAL) macules, Skeletal defects in NF1, Learning disabilities in NF1, Simvastatin treatment for cognitive deficits, Mosaicism for NF1 mutation, Diagnostic problems, SPRED1 mutations & molecular mechanism of Legius syndrome, The RAS pathway proteins & genetic syndromes (RASopathies)